DAMAGE DETECTION OF BEAM STRUCTURE USING DERIVED SENSITIVITY BASED ON STRUCTURAL FLEXIBILITY - ZHAO JingYun; YANG QiuWei; LI CuiHong; ZHANG Ying; LIANG ChaoFeng (Jixie qiangdu)
The flexibility-based damage identification methods have attracted much attention in structural engineering field in recent years. In this paper,three derived sensitivity methods based on structural flexibility are presented for damage identification,namely,the diagonal sensitivity,the principal eigenvector sensitivity and the unfavorable unit load distribution sensitivity. Compared with the original flexibility sensitivity technique,the effect of truncating higher-order modes can be partly reduced in the derived sensitivity methods. A three-span continuous beam was used to illustrate the feasibility and superiority of the derived sensitivity methods for structural damage detection. Results obtained by the first four modes and only the first mode are both given for comparison. When the first four modes are used,it is found that the principal eigenvector sensitivity and the flexibility sensitivity methods can achieve more accurate results than those obtained by the diagonal sensitivity and the unfavorable unit load distribution sensitivity techniques. When only the first mode is used,one can see that the principal eigenvector sensitivity and the unfavorable unit load distribution sensitivity techniques are more effective than the flexibility sensitivity and the diagonal sensitivity methods. Consequently,it is necessary to chose suitable sensitivity technique for the specific engineering problem to get satisfactory detection results.